Law and Justice in a Globalized World Proceedings of the Asia-Pacific Research in Social Sciences and Humanities, Depok, Indonesia, November 7-9, 2016 : Topics in Law and Justice - Un Oppusunggu, Yu; Juwana, Hikmahanto; Harkrisnowo, Harkristuti (Taylor & Francis, 2018)
The book consists of a selection of papers presented at the Asia-Pacific Research Conference on Social Sciences and Humanities. It contains essays on current legal issues in law and justice, and their role and transformation in a globalizing world. Topics covered include human rights, criminal law, law of the sea, good governance, democracy, foreign investment, and regional integration. The conference focused on Asia and the Pacific, two regions where law has taken an important position in creating and shaping the regional integrations, new legal institutions, and norms. This reconfirms the idea that the legal system is extremely important in the global world. This book provides new insights and new horizons on how law and justice took part in globalizing human interaction, especially in the Asia-Pacific region.